Assessment of the Conflict Prevention Capabilities of African Regional Economic Communities - Nations Unies (United Nations, 2020)
The Assessment of the Conflict Prevention Capabilities of African Regional Economic Communities (RECs) is an outcome of a six-month-long study that was commissioned by the Office of the Special Adviser on Africa (OSAA) to map out existing institutional capabilities and gaps, as well as entry points and opportunities, within the RECs in preventing conflicts and addressing the structural or root causes. The study is consistent with the renewed global and continental focus on conflict prevention, which the United Nations and the African Union have respectively identified as a priority for their individual and shared efforts to prevent violent conflicts, promote inclusive sustainable development, and sustain peace on the continent. Seven of the eight African RECs participated in the study, which mapped out their respective geopolitical context necessitating conflict prevention, their organizational or institutional structure, mandate, existing policies and framework documents on conflict prevention, tools and resources for conflict prevention, partnerships and collaboration on conflict prevention, their support to Member States in developing national and local conflict prevention capacities, and lessons learned in institutionalizing conflict prevention. The study covers both the operational and structural dimensions of conflict prevention and concludes with recommendations on key areas for bolstering the conflict prevention capabilities of the RECs.